Preparation and characterization of hydroxyapatite powder from biological natural bone - Sri Asliza, Md Amin; Shahrizal, Md Hussein; Zaheruddin, Kasmuin; Azida, Azmi; Siti Sarah, Ibrahim (Universiti Tun Hussein Onn Malaysia, 2011)
Organized by Universiti Tun Hussein Onn Malaysia (UTHM), 24th - 25th November 2008 at Hotel Katerina, Batu Pahat, Johor, Malaysia.